PENGATURAN SISTEM SHIFT KERJA UNTUK MENINGKATKAN PERFORMANCE SERTA MENGURANGI KELUHAN KARYAWAN - Fajarwati, Ferisia Dwi; Hidayat, Rachmad; Agustina, Fitri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Reduce fatigue and saturation levels of employees in a company's performance will affect the results and how they work in completing a job. Shift work system settings are useful for the company because with the shift work system will be able to improve performance and reduce employee complaints. Analyses were performed by the method of Analytical Hierarchy Process (AHP). Weighting the results indicate that the type of complaints for the morning shift caused by physical factors of 62 299%, with sub-criteria of 58 277% fatigue. On the night shift, the most influential type of complaint is the physical factor of 50 616%, with sub-criteria of fatigue by 59.1%. Setting a new work shift in the recommended improvements that include changes in rotation length. Arrangements made ​​by rotating shifts some employees who are divided into groups or group. Setting a new work shift system increases job performance of employees and reduce the level of employee complaints. Turnover shift work increases the sense of responsibility and work together as a team work. Shift work rotation to reduce employee complaints of fatigue in nature because the conditions of a monotonous work environment.